Developing countries : victims or participants : their changing role in international negotiations - Page, Sheila (Overseas Development Institute LondonGB, 2003)
Looks at what developing countries can gain from participatijng in negotiations and also at what makes them effective in negotiations. Examines how to use financial and technical assistance. Notes the increasing complexity of negotiations. Looks at how the international negotiations must adapt.